Electrochemical crystallization for recovery of phosphorus and potassium from urine as K-struvite with a sacrificial magnesium anode - Shan, Jinhua; Liu, Hongbo; Long, Shiping; Zhang, Haodong; Lichtfouse, Eric (Environmental chemistry letters, 2022)
Declining earth resources, rising ore cost and increasing pollution are calling for recycling of wastewater in the context of the circular economy. In particular, urine is a potential source of phosphorus (P) and potassium (K), yet currently available methods for P and K recovery are limited in efficiency. Here, we designed an electrochemical crystallization system using sacrificial magnesium anodes to recover P and K in the form of K-struvite (MgKPO 4 ·6H 2 O) from simulated urine at low (P/K = 0.25) and high (P/K = 0.6) phosphate levels, respectively. Results show optimal recoveries of 88.5% for P and 35.4% for K in the form of rod-shaped K-struvite at 3.5 mA/cm 2 , though higher current density reduced recovery due to side reactions and pH increase. Seeding prefabricated struvite crystals at 1.6 g/L into urine enhanced the recovery of K by 14.7% and of P by 23.7% compared to the control group. Overall, our findings show that electrochemical crystallization is promising to recover K-struvite fertilizers.